The Analysis of Natural Science Learning Misconceptions on Force, Motion, and Energy Materials In Elementary Schools - Rose Andriyani Saputri (International Journal of Social Service and Research, 2021)
This article discusses about the misconceptions occurred in elementary school, especially on force, motion, and energy. Misconceptions often occur in students due to a lack of the teacher's understanding of the material. However, teachers have to understand the material that will be delivered to students so that there are no misconceptions among students. In this article, the researchers took samples of elementary school teachers in the Jatipuro District. In this study, 55 respondents had filled out a questionnaire regarding force, motion, and energy. The results of the study showed, there were still teachers who still experience natural science learning misconceptions, especially on force, motion, and energy. Relating to force, motion, and energy, they experienced misconceptions that cause students to experience misconceptions about natural science learning. Thus, it needs to be followed up so that future generations can understand knowledge following the actual concept so that they can create results that can help their daily life. On the other hand, the role of various parties is needed so that mistakes in the natural science concept do not take place continuously. One of the efforts to stop misconceptions in natural science learning is to conduct research on these misconceptions and then repair them so that there will be changes that can change our lives in the future